Discovery of Single Nucleotide Polymorphisms (SNPs) as a tool for markerassisted breeding of cassava, Manihot esculenta - Gedil, Melaku A; Igwe, D. (International Association of Hydrological Sciences, 2012)
Discovery of single nucleotide polymorphisms, (SNPs) as a tool in marker-assisted breeding of cassava, Manihot esculenta was studied. The principal objective of this study is to discover single nucleotide polymorphisms (SNPs) in some panels of elite lines (ELs) of cassava and in some mapping populations to be used as a tool for marker-assisted breeding in cassava (Manihot esculenta). As a nucleotide base constitutes genetic information for inheritance, SNPs provide the ultimate form of molecular genetic markers. Small insertion or deletion occurrences (indel for insertion/deletion) are other factors that bring about genetic mutations. These mutations may be detected as SNPs as the insertion or deletion of nucleotides changes the sequence read. The rapid advance of the sequencing technology and the steadily declining cost of sequencing prompted the development of a gamut of SNP discovery and genotyping technologies. A panel of ELs and three mapping populations (TME3xTME117, TME3x30555 and TME14x96/1089A) were used. Six full gene sequences (both nuclear and chloroplast genes), involved in starch, sucrose, and cyanogenic glucoside biosynthesis, and three promoter sequences were used for designing primers. Single nucleotide polymorphism analysis of a total of 9,993 base pairs of sequence revealed 184 SNP sites and 43 InDels, giving rise to frequencies of 1 SNP per 54 bp and 1 SNP per 232 bp respectively. Exonic and intronic regions were identified to be 106 and 78 respectively. Synonymous and non-synonymous changes were identified using Codon-based Test of Neutrality. The frequency of SNPs was much higher than that of the InDels. The polymorphisms observed were due to the effects of transitions (C/T or A/G), transversions (C/G, A/T, A/C or G/T), hetero zygosities and the occurrence of InDels within the sequenced samples. A total of 126 polymorphisms (68.5%) were transitions (C/T or A/G) and 58 polymorphisms (31.5%) were transversions (C/G, A/T, A/C, or G/T). Analysis of preference using Z test of selection for estimation of synonymous substitutions per synonymous sites (dS) and n o n s y n o n y m o u s s u b s t i t u t i o n s p e r nonsynonymous sites (dN) was also done on TME14 x 96/1089A. The dN (306.7) > dS (125.5) was noted showing that positive selection is operating within the genes used. Parentage of F1 hybrids of TME14X96/1089A was verified using SNPs generated from four genes out of the aforementioned number of genes used in this study and these highly informative primers not only differentiated the parent genotypes but also confirmed the parentage of their true F1 hybrids.